ZNF32 histidine 179 and 183 single-site and double-site mutations promote nuclear speckle formation but differentially regulate the proliferation of breast cancer cells - Zhong, Chaosong; Chen, Dingshuang; Wang, Fei; Wang, Junqi; Li, Ruiwen; Li, Yanyan; Gong, Di (Frontiers in Cell and Developmental Biology, 2025)
Studies have shown that histidine 179A and 183A (H179, 183A) of the ZNF32 protein exhibit point-like nuclear speckles, but the causes of such speckle formation and their effects on breast cancer cells remain unknown. In this study, we prepared breast cancer cells containing ZNF32 H179, 183A, H179A, and H183A and observed nuclear speckles in all three cell types. Transcriptome analysis showed that these nuclear speckles may be related to changes in the activities of the cell growth factor and RNA polymerase II transcription factor. Comprehensive transcriptomics and metabolomics analyses showed that the formation of ZNF32 nuclear speckles was accompanied by changes in choline metabolism. Both in vivo and in vitro experiments suggested that ZNF32 H179A and H183A but not H179, 183A could promote breast cancer cell proliferations. We then explored and verified the differentially expressed genes through RNA-seq and RT-qPCR to explain the different proliferation abilities of these mutations. The dual luciferase reporter gene assay confirmed that ZNF32 H179A and H183A could transcriptionally activate ISY1-RAB43 and UPK3BL1 while inhibiting the transcription of SNX22; this is attributable to the fact that these mutations cause different zinc finger structure changes in ZNF32. The present study deepens the understanding of ZNF32 mutations with respect to nuclear speckle formation and their roles in the proliferation of breast cancer cells.